PELAKSANAAN TUGAS LAUNDRY ATTENDANT DI HOUSEKEEPING DEPARTMENT HOTEL GRAND ZURI DI KECAMATAN MANDAU - Farah, Muktia; ', Etika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is entitled Implementation of Laundry Attendant Duties in the Housekeeping Department of the Grand Zuri Hotel in Mandau District. This research aims to find out how the Laundry Attendant's duties are carried out in the Housekeeping Department of the Grand Zuri Hotel in Mandau District, and what obstacles the Laundry Attendants face in carrying out their duties in the Housekeeping Department of the Grand Zuri Hotel in Mandau District, and what are the solutions for facing obstacles when carrying out their duties Laundry Attendant at the Housekeeping Department of the Grand Zuri Hotel in Mandau District. This research uses a qualitative method with a descriptive approach used in this research, with data collection techniques used in this research in the form of observation, interviews and documentation. Key informants involved in this research were Housekeeping Supervisor, Laundry Attendant, personnel department, Purchasing, and guests. Based on research results, the implementation of Laundry Attendant duties in the Housekeeping Department of the Grand Zuri Hotel in Mandau District has been running well and in accordance with the Standard Operating Procedure (SOP). But of course there are definitely obstacles faced by the Laundry Attendant in the Housekeeping Department of the Grand Zuri Hotel in Mandau District, such as when sorting and counting linen, when distributing linen, when inventorying linen, when repairing linen, and when storing linen, but these are the obstacles faced by Laundry Attendants in the Housekeeping Department can be handled with the best solutions. Keywords: Grand Zuri Hotel in Mandau District, Implementation of Duties, Laundry Attendant, Housekeeping Department.